The Application of Various Types of Sharia Contracts in Cross-Border Transactions: A Sharia Economic Law Perspective - Khoiriyah, Nadzirotul Fuadatil; Asiyah, Binti Nur; Nasution, Addriana Della; Munna, Nurul Isna Faizatul; Isa, Mohamad Yazid (Universitas Islam Negeri Raden Intan Lampung, 2026)
Rapid global economic development has increased the intensity of cross-border transactions, which in turn demands an adaptive and comprehensive legal framework, including from the perspective of Sharia Economic Law. This study aims to analyze the application of various types of Sharia contracts in cross-border trade transactions, identify variations of operationally relevant contracts, and unravel the accompanying legal issues and challenges. This study uses a normative legal method (literature study) with a conceptual, legislative, and Sharia compliance approach. Data are sourced from journal literature, fatwas, and international standard regulations (such as AAOIFI and the United Nations Convention on Contracts for the International Sale of Goods/CISG). The results show that Sharia-compliant cross-border transactions are implemented through various instruments such as Sharia Letters of Credit (L/C), trade finance instruments, and the adoption of smart contracts, with the dominant use of Murabahah, Wakalah, Kafalah, and Sharf (foreign exchange) contracts. However, the implementation of these contracts faces crucial issues related to legal harmonization, differences in jurisdictions and legal systems across countries, the enforcement of foreign Sharia arbitration awards, and the challenge of eliminating gharar elements in global trade standards such as Incoterms. It can be concluded that harmonization of international trade instruments with the principles of Islamic jurisprudence (fiqh) is essential to provide legal certainty, protect the parties, and guarantee universal Sharia compliance.